Change of Orthopedics Referred Cases to Chiang Rai Regional Hospital during 2003-2007 - Utaipiboon, Somsak; Jarasdamrongwat, Sathorn; Somyaraj, Sumitra; Srivilai, Suthat (Journal of Health Science of Thailand, 2018)
Changes of social and health care system in Thailand during the previous 5 years can lead to increasing number of orthopedics cases in tertiary care hospitals. This retrospective descriptive and analytic study was conducted in order to clarify a magnitude of problems on orthopedics referral from nearby hospitals to Chiang Rai Regional Hospital (CRRH) in order to define evidence for further plan. Medical records of In-Patient Department (IPD) Orthopedics referred cases from fiscal year 2003 to 2007 were reviewed with objectives to quantify number and trend, diseases, length of stay (LOS), cost, and factors associated with haphazard referrals of orthopedics case during the 5 years. There were 15,729 cases referred mostly with fracture of lower end of radius, fracture of shaft of tibia, and pertrochanteric fracture. Among top ten orthopedics injuries, trend of referred numbers remained constant showing increasing profile only on open wound of other parts of wrist and hand and fracture of other fingers. LOS was the longest in cases of fracture of neck of femur (11 days) and fracture of lower end of radius is lowest (2 days). Whereas a declining trend of LOS was observed, cost of treatment climbed up during the 5 years. Fifty to sixty percent were referred without being in line with Interhospital Triage Criteria as such, factors associated with such noncompliance were, referred cases in years 2004-2007 compared with 2003 (OD=1.2, p<0.005) and distance between hospitals to CRRH < 50 kms (OD=1.1, p<0.05).